Chaotic dynamics of string around the charged Kiselev black hole - Kai Li; Da-Zhu Ma; Zhen-Meng Xu (Physics Letters B)
Dynamics of a string near the event horizon of the charged Kiselev black hole is studied in this paper. From the results of the Lyapunov indicator, we find that the chaotic dynamics evolution of the string evolves very frequently, and the violation of the MSS (Maldacena, Shenker, Stanford) limit often occurs. It is shown that the motion of the string is significantly impacted by the angular momentum and energy. No matter how the angular momentum changes, the motion of the string is always chaotic. However, the movement of the string gradually becomes orderly as the energy increases. Thus, our new conclusions differ entirely from the particle. In the same black hole background, for the particle, the small angular momentum produces periodic motion, while the large angular momentum generates chaos.